Updating the Phases of Journalistic Content for Mobile Devices - Silva-Rodríguez, Alba (2022)
Mobile devices have acquired an increasingly prominent role within the media arena. The consolidation of smartphones as the preferred platforms to access digital journalistic information has led to a number of changes in how the news is produced, distributed and eventually consumed. This article describes an evolving model of journalistic content for mobile devices to contribute to the theory of mobile media already set in motion by other peer researchers. Framed within the media ecology, the actor-network theory and the study of the society-technology relationship, we start with a bibliographic review to analyse innovations in the mobile digital ecosystem that are related to semantics (new formats and content genres) and social aspects (new forms of appropriation of media and technologies) whilst also identifying the main actors currently operating in this ecosystem. This approach makes it possible to reconstruct the emergent process that affected mobile technologies, devices, uses, platforms, products and services on a multidimensional timeline. A new stage in mobile journalism was defined and characterized from 2015 onwards. The consolidation phase for journalistic content on mobile devices is defined by the rise of social networks and micro-formats, personalization, video, audio, newsletters and news alerts, wearables, smart speakers and automation. At this stage, the production of informative content specifically designed to be distributed through various mobile devices was normalized, which led to the adaptation of old formats and the appearance of new ones.